Monaco : Assessment of the Supervision and Regulation of the Financial Sector Volume II--Detailed Assessment of Observance of Standards and Codes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The detailed assessments of the Offshore Financial Center Assessment of Monaco reviews the assessments of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) related principles of the Basel Core Principles for Effective Bank Supervision, of the AML/CFT regime based on the Bank/IMF Draft Methodology, and of securities regulation on the basis of the International Organization of Securities Commissions Objectives (IOSCO) and Principles of Securities Regulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet